Synthesis and Evaluation of L-glutamide Derived Carbonyl Group Containing RP-HPLC Phase for Polycyclic Aromatic Hydrocarbon (PAH) Separation (Bangladesh Journal of Scientific and Industrial Research, 2011)
A new L-glutamide derived internal C=O group containing HPLC stationary phase was synthesized. The L-glutamide lipid was immobilized on to silica surface through aminopropyltrimethoxysilane (APS) linker. The detailed chemical structure of the compounds leading to the final lipid was characterized by melting point measurement, FTIR, 1H NMR and elemental analysis in each step. Chromatographic properties of silica immobilized N-(pyrinylbutyric) L-glutamic acid, Sil-PBG, were evaluated under reversed phase conditions by separation of different polycyclic aromatic hydrocarbons (PAHs) and the results were then compared with monomeric octadecylated silica stationary phase (ODS). Chromatographic evaluation of the new phase showed promising results for the separation of PAHs. Key words: L-glutamide lipid; RP-HPLC; Enhance selectivity; Polycyclic aromatic hydrocarbonsDOI: http://dx.doi.org/10.3329/bjsir.v46i3.9031BJSIR 2011; 46(3): 271-276